Formal and informal support networks as sources of resilience and sources of oppression for temporary foreign workers in Canada. (14th December 2022) - Salami, Bukola; Tulli, Mia; Alaazi, Dominic A; Juen, Jessica; Khasanova, Nariya; Foster, Jason; Vallianatos, Helen
Abstract: In this article, we explore temporary foreign workers' (TFWs) access to and experiences with formal and informal supports in Canada. Our study utilized a participatory action research design and four overlapping phases of data collection: individual interviews with current and former TFWs, focus groups, individual interviews with settlement service agencies, and a cross-sectional survey with current and former TFWs. We used an intersectional theoretical framework to analyze these data and explore ways that TFWs interact with formal and informal sources of support for navigating their precarious immigration status and integration in Canada. Our findings show these supports have the potential to both benefit and harm TFWs, depending on their social positioning and availability of institutional resources. The benefits include information that aids settlement and integration processes in Canada, while the harms include misinformation that contributes to status loss. Future research and policy should recognize the complexity of informal and formal support networks available to TFWs. An absence of government support is apparent, as is the need for increased funding for settlement service agencies that serve these workers. In addition, Canada should better monitor employers, immigration consultants, and immigration lawyers to ensure these agents support rather than oppress TFWs.